A New Classification of the Lateral Dermatochalasis of Upper Eyelids. Issue 7 (23rd July 2021) - Rossi Santos Silva, Kennedy; Cardoso Rossi, Débora; Petroianu, Andy
Abstract : Background: Eyelid dermatochalasis is an abnormal distention of the upper eyelid. This article presents a new classification of the lateral dermatochalasis (LDC) of the upper eyelids, which compares the pre- and post-blepharoplasty results and matches its results with those of the well-established Jacobs classification (JEC). Methods: LDC classification includes four degrees: grade zero—absence of dermatochalasis; grade 1—lower edge of dermatochalasis above the intersection of the lacrimal caruncle with the edge of the upper eyelid; grade 2—between the intersection of the lacrimal caruncle with the edge of the upper eyelid and the lower edge of the iris at the pupillary midpoint; and grade 3—lower edge of dermatochalasis below the lower edge of the iris. This study was conducted in 100 dermatochalasis cases in patients between 38 and 79 years of age (mean = 59.3) and submitted to upper blepharoplasty. Results: No statistically significant association was found between the LDC and JEC methods ( P = 0.583). In both classifications, the eyelid dermatochalasis was reduced after blepharoplasty ( P < 0.001). However, changes in the degrees of dermatochalasis before blepharoplasty were detected in 100% by LDC, and 41% by JEC. The degree of improvement of dermatochalasis observed by LDC after blepharoplasty showed greater specificity. Conclusions: This new classification, LDC, is specific for the lateral eyelid dermatochalasis, which is based on exact anatomical points, and is easy to perform. LDC is superior to JEC, easy to be applied, and effective and specific in detecting variations in dermatochalasis after blepharoplasty.